KONVERGENSI IFRS DI INDONESIA: PENGARUH PENERAPAN STANDAR PENGENDALIAN MUTU KANTOR AKUNTAN PUBLIK TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI SALAH SAJI MATERIAL - Chairul Wismoyo; Murtanto Murtanto (Jurnal Magister Akuntansi Trisakti, 2014)
Convergence of International Financial Reporting Standards (IFRS) in Indonesia requires certified public accountant (CPA) for update their knowledge on Statements of Financial Accounting Standards (PSAK) all the time. Auditors’ knowledge on PSAK is very important for performing high quality audit. CPA firm is trying to maintain the audit quality by applying auditing standards on quality control established by the Indonesian Institute of Certified Public Accountant (IAPI). This study examined the relationship and effectiveness of the policies and procedures for each component of quality control standard on the auditors’ ability to detect material misstatement in the financial statements applying PSAK from IFRS convergence. The study presents that quality control standard contributes 65% of auditors’ knowledge on PSAK whereby policies and procedures of inspection provide strongest contribution compared to the policies and procedures related to the independence, consultation, supervision, professional development, and promotion. The study also presents that the professional development in the form of class-training or on-the-job training is the most effective way to improve PSAK knowledge.